245 Associations between patient acceptable symptom stateand three domains of the disease in SLE: a cross-sectional study of 1, 364 patients from the spanish society of rheumatology lupus registry. (April 2019) - Vazquez Rodriguez, Tomas R; Figueroa, Iñigo Rua; Perez, Victor Del Campo; Narváez-García, Javier; López-Longo, Francisco Javier; Izquierdo, Maria Galindo; Alen, Jaime Calvo; Nebro, Antonio Fernandez; Ovalles-Bonilla, Juan; Muñoz, Paula Rubio; Muriel, Eva Tomero; Rodriguez, Coral Mouriño; et al.
Abstract : Background: In a large cohort of systemic lupus erythematosus (SLE) patients, to evaluate the association between a Patient Acceptable Symptom State (PASS) and three different domains of the disease: activity, damage and impact of SLE on patients lives. Methods: Cross-sectional study of 1, 364 SLE (ACR 97 Criteria) patients from the Spanish Society of Rheumatology Lupus Registry (RELESSER). Patients were clinically assessed by the physicians, who collected data about demographics, clinical manifestations, laboratory features and therapies. SLE activity was assessed by using the SLEDAI (SLE Disease Activity Index). The Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SLICC/ACR DI) was used to measure damage accrual. The impact of SLE on patients lives was evaluated by using the Lupus Impact Tracker (LIT). Finally, the PASS question 'Considering all the different ways your disease is affecting you, if you would stay in this state for the next months, do you consider that your current state is satisfactory? was answered in a dichotomized way: yes/no. Measures of central tendency and spread were used to describe responses and T-test was used to evaluate the independence between PASS and the other questionnaires and indices. Results: Mean age (years)±S.D. of the 1364 patients included in the study was 49.9±13.3; 90.3% were female and 94.9% were Caucasian. In the total of patients, 979 (71.8%) were in PASS. Patients in PASS had significantly lower activity (SLEDAI Score) than those not in PASS (2.4±3.2 vs. 3.0±3.9, respectively; p=0.007). The SLICC/ACR DI was significantly lower in the group of patients in PASS compared to those without PASS (0.64±1.1 vs. 0.81±0.21, respectively; p=0.022). SLE had a significantly lower impact on patients in PASS in comparison to those without PASS (LIT Score: 8.47±7.5 vs. 19.8±8.34, respectively; p=0.001). Distribution and statistics for each group are shown in table 1 . Conclusions: In the largest observational European Registry of SLE patients, PASS was associated with other domains of the disease: activity, damage and impact on patients life. PASS is a simple and reliable patient-reported outcome that can be a useful tool to evaluate patients well-being. Funding Source(s): None